Effect of the Baseline Vitamin D Level on Growth Outcome in Pediatric Crohn Disease - Lee, Eun Joo (Pediatr Gastroenterol Hepatol Nutr, 2017)
PURPOSE: Vitamin D deficiency is common in Crohn disease (CD). The aim of the study was to examine the prevalence of vitamin D deficiency and evaluate the association between vitamin D status and growth outcome in Korean pediatric CD patients. METHODS: In this retrospective study, 17 children younger than 18 years old diagnosed with CD were enrolled and their serum 25-hydroxy vitamin D (25[OH]D) was checked between 2011 and 2015. We categorized the patients into two groups, Group 1 and Group 2. Group 1 included patients with serum 25(OH)D levels below 10 ng/mL, and Group 2 was for patients with a 25(OH)D serum levels between 10 ng/mL and 30 ng/mL. The z-scores for height (Htz), weight (Wtz), and body mass index (BMIz) were measured at baseline, 6 months, and 12 months. RESULTS: The mean serum 25(OH)D levels of the total 65 CD patients and 17 enrolled patients were 15.64±6.9 ng/mL and 13.1±5.1 ng/mL, respectively. There was no correlation at the beginning of the study between vitamin D level and growth parameters (Htz, Wtz, BMIz) or other variables including laboratory data and Pediatric Crohn Disease Activity Index. The Htz, Wtz, and BMIz in Group 1 showed no significant improvement at 6 months and 12 months follow-up. In Group 2, Wtz and BMIz showed significant improvements sustained until 12 months of follow-up. Htz showed no significant improvement at 6 months but there was significant improvement at 12 months. CONCLUSION: It seems that baseline vitamin D status affects growth outcome in pediatric CD.